FOREL-Wegweiser: Handlungsempfehlungen für den ressourceneffizienten Leichtbau - Göddecke, Johannes; Meschut, Gerson; Gude, Maik; Lieberwirth, Holger; Tekkaya, Erman; Zaeh, Michael; Stegelmann, Michael; Müller, Michael; Böhme, Kurt; Krampitz, Thomas; Zöllner, Mareen; Hahn, Marlon; et al.

Experimentelle und numerische Untersuchung der Dämpfungseigenschaften geklebter Strukturen unter dynamischer Beanspruchung - Göddecke, Johannes; Meschut, Gerson; Teutenberg, Dominik; Ummenhofer, Thomas; Albiez, Matthias; Damm, Jannis; Matzenmiller, Anton; Kötz, Fabian (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Entwicklung und Qualifizierung einer rechnergestützten Auswertemethode zur Differenzierung der Versagensanteile klebtechnisch gefügter Proben - Ditz, Michael; Meschut, Gerson; Schwarze, Thomas; Smart, Dominic

The Interdisciplinary Development of an Educational Game for Primary School Children--Lessons Learned - Winkelnkemper, Felix; Schulte, Carsten; Eilerts, Katja; Bechinie, Dominik; Huhmann, Tobias (EdMedia+ Innovate Learning)

Specification of Software Requirements for Condition Monitoring of Automation Systems - Pasic, Faruk; Wohlers, Benedict (2020 IEEE Tenth International Model-Driven Requirements Engineering (MoDRE))

Aligning Strategy and Structure for Smart Service Businesses in Manufacturing - Koldewey, Christian; Gausemeier, Jürgen; Chohan, Nadia; Frank, Maximilian; Reinhold, Jannik; Dumitrescu, Roman (Proceedings of the IEEE International Conference on Technology Management, Operations and Decisions ”Disruptive Technologies and Social Impacts”)

Systematische Entwicklung von Normstrategien für Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen; Bäsecke, Alexander; Reinhold, Jannik; Dumitrescu, Roman (ZWF Zeitschrift für wirtschaftliche Fabrikplanung)
Die Verfügbarkeit von Daten aus dem Betrieb hat durch die Einführung von vernetzten intelligenten Fertigungssystemen (cyber-physische Systeme) stark zugenommen. Hieraus eröffnen sich Erfolg versprechende Möglichkeiten für Smart Services und damit verbundene neue Geschäftsfelder. Voraussetzung für den Eintritt in ein neues Geschäft mit Smart Services ist eine fundierte Geschäftsstrategie. Wir zeigen die zentralen Gestaltungsfelder von Smart Service-Strategien auf und erläutern, wie sechs von uns ermittelte Normstrategien bei der Formulierung einer attraktiven Strategie helfen können.
Keywords: Smart Service; Digitalisierung; Industrie 4.0

Planning a Smart Service Business Integrating External Partners - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Managing Digital Open Innovation)
Today’s manufacturing industry is confronted with fundamental changes in value creation. The tension between the two megatrends of digitization and servitization leads to new hybrid market offerings, so-called smart services. Corresponding business models and value networks fundamentally differ from traditional ones. Developing smart services requires an advanced management of business models and new competences in young disciplines, while their provision requires new internal and external organizational structures or processes. To strengthen their competitive position, manufacturing companies need to extend their business model portfolios and adapt their value networks. However, the highly complex transformation of value creation especially challenges small and medium-sized companies due to limited competences and resources. They must consider opening their boundaries and collaborating with partners. In this chapter, we introduce a basic framework for designing smart services and present a methodology for the planning of a smart service business integrating external partners. The methodology is structured into five phases: Examination of smart service portfolio, analysis of business models and environment, business model portfolio planning, competence identification and analysis, and value creation planning. The methodology is explained by an example on cable marker printers.
Keywords: Smart Service; Digitalisierung; Industrie 4.0

Light diffraction in slab waveguide lenses simulated with the stepwise angular spectrum method - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optics Express)
A stepwise angular spectrum method (SASM) for curved interfaces is presented to calculate the wave propagation in planar lens-like integrated optical structures based on photonic slab waveguides. The method is derived and illustrated for an effective 2D setup first and then for 3D slab waveguide lenses. We employ slab waveguides of different thicknesses connected by curved surfaces to realize a lens-like structure. To simulate the wave propagation in 3D including reflection and scattering losses, the stepwise angular spectrum method is combined with full vectorial finite element computations for subproblems with lower complexity. Our SASM results show excellent agreement with rigorous numerical simulations of the full structures with a substantially lower computational effort and can be utilized for the simulation-based design and optimization of complex and large scale setups.
Keywords: tet_topic_waveguides

Lebensdauerberechnung hybrider Verbindungen - Çavdar, Serkan; Teutenberg, Dominik; Meschut, Gerson; Wulf, A.; Hesebeck, O.; Brede, M.; Mayer, B.; Tittmann, K.; Koch, I.; Jäger, H.; Wacker, J.-D.; Rybar, G.; et al. (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Berechnen der Lebensdauer hybrider Verbindungen - Çavdar, Serkan; Meschut, Gerson; Wulf, A.; Hesebeck, O.; Brede, M.; Mayer, B.; Tittmann, K.; Koch, I.; Jäger, H.; Wacker, J.-D.; Rybar, G.; Melz, T. (DVS Congress 2020)

Fatigue life prediction of adhesively bonded FRP-aluminium-joints with hyperelastic behavior under cyclic multiaxial stress state - Çavdar, Serkan; Meschut, Gerson; Wulf, A.; Hesebeck, O.; Brede, M.; Mayer, B. (Joining in Car Body Engineering 2020)

Prozesskettenbegleitende Vorgehensweise beim Mechanischen Fügen - Heyser, Per; Scharr, Christian; Nehls, Thomas; Wiesenmayer, Sebastian; Flügge, Wilko; Meschut, Gerson (4. Workshop Digitalisierung)

Hamstrings substitution via anteromedial portal with optional anterolateral ligament reconstruction is the preferred surgical technique for anterior cruciate ligament reconstruction: a survey among ESSKA members. - Vascellari, A; Grassi, A; Canata, GL; Zaffagnini, S; Gokeler, A; Jones, H (Knee Surg Sports Traumatol Arthrosc)

Sagittal knee kinematics in relation with the posterior tibia slope during jump landing after an anterior cruciate ligament reconstruction. - Keizer, MNJ; Hijmans, JM; Gokeler, A; Otten, E; Brouwer, RW (J Exp Orthop)

Healthy subjects with lax knees use less knee flexion rather than muscle control to limit anterior tibia translation during landing. - Keizer, MNJ; Hijmans, JM; Gokeler, A; Benjaminse, A; Otten, E (J Exp Orthop)

Functional progression milestones following anterior cruciate ligament reconstruction are more appropriate than time-based criteria: a survey among the ESSKA. - Vascellari, A; Gokeler, A; Grassi, A; Canata, GL; Zaffagnini, S; Jones, H (Knee Surg Sports Traumatol Arthrosc)

Younger age and hamstring tendon graft are associated with higher IKDC 2000 and KOOS scores during the first year after ACL reconstruction. - Magnitskaya, N; Mouton, C; Gokeler, A; Nuehrenboerger, C; Pape, D; Seil, R (Knee Surg Sports Traumatol Arthrosc)

Passing return to sports tests after ACL reconstruction is associated with greater likelihood for return to sport but fail to identify second injury risk. - Welling, W; Benjaminse, A; Lemmink, K; Gokeler, A (Knee)

Towards Smart V2X-Connected Powertrains - Eisenbarth, Markus; Wegener, Marius; Scheer, René; Andert, Jakob; Buse, Dominik S.; Klingler, Florian; Sommer, Christoph; Dressler, Falko; Reinold, Peter; Gries, Rafael (IEEE Vehicular Technology Magazine (VTMag))

An Open Source Approach to Field Testing of WLAN up to IEEE 802.11ad at 60 GHz Using Commodity Hardware - Klingler, Florian; Hauptmeier, Fynn; Sommer, Christoph; Dressler, Falko (39th IEEE International Conference on Computer Communications (INFOCOM 2020), Poster Session)

Modern WLAN for V2X Applications: Exploiting Beamforming for Platooning - Hardes, Tobias; Klingler, Florian; Sommer, Christoph (12th IEEE Vehicular Networking Conference (VNC 2020))

Poster: Towards 2-Hop Neighbor Management for Heterogeneous Vehicular Networks - Turcanu, Ion; Kim, Minsuk; Klingler, Florian (12th IEEE Vehicular Networking Conference (VNC 2020))

Einfach den blauen Knopf drücken - Die Universität Paderborn entschied sich bereits Mitte März für Big Blue Button, ein offenes Videokonferenz-System, mit dem sich auch Lehr- und Lernprozesse unterstützen lassen - Oevel, Gudrun; Odenbach, Christopher (DUZ Wissenschaft & Management)

Method for data inventory and classification - Massmann, Melina; Meyer, Maurice; Frank, Maximilian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Data-Driven Product Generation and Retrofit Planning - Meyer, Maurice; Frank, Maximilian; Massmann, Melina; Wendt, Niklas; Dumitrescu, Roman (Procedia CIRP)

Datengetriebene Steigerung der Verfügbarkeit - Uhlmann, Eckart; Dumitrescu, Roman; Polte, Julian; Meyer, Maurice; Simsek, Deniz (wt Werkstattstechnik online)

Framework for Data Analytics in Data-Driven Product Planning - Massmann, Melina; Meyer, Maurice; Frank, Maximilian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia Manufacturing)

Combining Ideas and Artifacts: An Interaction-Focused View on Computing Education Using a Cybersecurity Example - Terfloth, Lutz; Budde, Lea; Schulte, Carsten
In this paper, we present a novel approach to design teaching interventions for computing education, elaborated using an example of cybersecurity education. Cybersecurity education, similar to other computing education domains, often focuses on one aspect and separate themselves from the other approach. In other words, they focus on one of the two different aspects: a) either teaching how to use and to behave, or b) how technology works. Here we suggest another point of focal awareness for teaching – interaction – that allows the recombination of both approaches in a novel way, leading to a reconstruction of the teaching and learning content in a way that – as we hope – supports an understanding on a higher level and thus gives the chance to better develop agency. For this didactic reconstruction of teaching content, we use an approach called the hybrid interaction system framework. In cybersecurity training, teaching interventions oftentimes are in a way successful but seem to not lead to long-lasting changes towards secure behavior. Using simply password security as an example, we show how this new approach recombines the two different priory mentioned teaching approaches in a novel way. Within this short paper, we present our current research progress, discuss potentials and values of the approach in general, and by way of example. Our intention of this submission and early disclosure is to spark discussion and generate further insights especially regarding the following question: What implications does the hybrid interaction system approach have on learning scenarios?

Balance task difficulty affects postural sway and cortical activity in healthy adolescents. - Gebel, A; Lehmann, T; Granacher, U (Exp Brain Res)

Platelet-rich plasma (PRP) as therapy for cartilage, tendon and muscle damage - German working group position statement. - Tischer, T; Bode, G; Buhs, M; Marquass, B; Nehrer, S; Vogt, S; Zinser, W; Angele, P; Spahn, G; Welsch, GH; Niemeyer, P; Madry, H (J Exp Orthop)

The influence of motor tasks and cut-off parameter selection on artifact subspace reconstruction in EEG recordings - Anders, P; Müller, H; Skjæret-Maroni, N; Vereijken, B; Baumeister, Jochen (Medical & Biological Engineering & Computing)

A self stabilizing protocol for well-formed trees in hybrid networks - Jochmaring, Moritz

Impact of Chlorine on the Internal Transition Rates and Excited States of the Thermally Delayed Activated Fluorescence Molecule 3CzClIPN - Streiter, Martin; Fischer, Tillmann G.; Wiebeler, Christian; Reichert, Sebastian; Langenickel, Jörn; Zeitler, Kirsten; Deibel, Carsten (The Journal of Physical Chemistry C)
Keywords: pc2-ressources

A photoredox catalysed Heck reaction via hole transfer from a Ru(II)-bis(terpyridine) complex to graphene oxide - Rosenthal, Marta; Lindner, Jörg K N; Gerstmann, Uwe; Meier, Armin; Schmidt, W Gero; Wilhelm, René (Royal Society of Chemistry)

A systematic literature review of model-driven security engineering for cyber–physical systems - Geismann, Johannes; Bodden, Eric (Journal of Systems and Software)

Explaining Static Analysis with Rule Graphs - Nguyen Quang Do, Lisa; Bodden, Eric (IEEE Transactions on Software Engineering)

PASAPTO: Policy-aware Security and Performance Trade-off Analysis - Computation on Encrypted Data with Restricted Leakage - Fischer, Andreas; Janneck, Jonas; Kussmaul, Jörn; Krätzschmar, Nikolas; Kerschbaum, Florian; Bodden, Eric (2020 IEEE Computer Security Foundations Symposium (CSF))

Heaps'n Leaks: How Heap Snapshots Improve Android Taint Analysis - Benz, Manuel; Krogh Kristensen, Erik; Luo, Linghui; P. Borges Jr., Nataniel; Bodden, Eric; Zeller, Andreas (International Conference for Software Engineering (ICSE))

Computation on Encrypted Data using Dataflow Authentication - Fischer, Andreas; Fuhry, Benny; Kerschbaum, Florian; Bodden, Eric (Privacy Enhancing Technologies Symposium (PETS/PoPETS))

CogniCrypt_GEN - Generating Code for the Secure Usage of Crypto APIs - Krüger, Stefan; Ali, Karim; Bodden, Eric (International Symposium on Code Generation and Optimization (CGO))

CogniCrypt -- The Secure Integration of Cryptographic Software - Krüger, Stefan
Frühere Studien haben empirisch offenbart, dass Fehlbenutzungen von kryptographischen APIs in Softwareanwendungen weitverbreitet sind. Dies geschieht vor allem, weil Software-Entwickler_innen aufgrund schlechten API-Designs und fehlenden Kryptographiewissens Probleme bekommen, wenn sie versuchen kryptographische Features zu implementieren. Die Literatur liefert mehrere Ansätze und Vorschläge diese Probleme zu lösen, aber alle scheitern schlussendlich auf die eine oder andere Weise daran die Anforderungen der Entwickler_innenzu erfüllen. Das Resultat ist eine insgesamt lückenhafte Landschaft verschiedener nur wenigkomplementärer Ansätze.In dieser Arbeit adressieren wir das Problem kryptographischer Fehlbenutzungen systematischer durch CogniCrypt. CogniCrypt integriert verschiedene Arten von Tool Supportin einen gemeinsamen Ansatz, der Entwickler_innen davon befreit wissen zu müssen, wie diese APIs benutzt werden müssen. Zentral für unseren Ansatz ist CrySL, eine Beschreibungssprache,die die kognitive Lücke zwischen Kryptographie-Expert_innen und Software-Entwickler_innenüberbrückt. CrySL ermöglicht es Kryptographie-Expert_innen zu spezifizeren, wie die APIs,die sie bereitstellen, richtig benutzt werden. Wir haben einen Compiler für CrySL implementiert, der es erlaubt auf CrySL-Spezifikationen aufbauenden Tool Support zu entwickeln. Wir haben weiterhin die statische Analyse CogniCrypt_SAST und den Code-Generator CogniCrypt_GEN entwickelt. Schlussendlich haben wir CogniCrypt prototypisch implementiert und diesen Prototyp in einem kontrollierten Experiment evaluiert.

Model-driven engineering and usability evaluation of self-adaptive user interfaces - Yigitbas, Enes (ACM SIGWEB Newsletter)

Cutting through the Jungle: Disambiguating Model-based Traceability Terminology - Holtmann, Jörg; Steghofer, Jan-Philipp; Rath, Michael; Schmelter, David (2020 IEEE 28th International Requirements Engineering Conference (RE))
Traceability, a classic requirements engineering topic, is increasingly used in the context of model-based engineering. However, researchers and practitioners lack a concise terminology to discuss aspects of requirements traceability in situations in which engineers heavily rely on models and model-based engineering. While others have previously surveyed the domain, no one has so far provided a clear, unambiguous set of terms that can be used to discuss traceability in such a context. We therefore set out to cut a path through the jungle of terminology for model-based traceability, ground it in established terminology from requirements engineering, and derive an unambiguous set of relevant terms. We also map the terminology used in existing primary and secondary studies to our taxonomy to show differences and commonalities. The contribution of this paper is thus a terminology for model-based traceability that allows requirements engineers and engineers working with models to unambiguously discuss their joint traceability efforts.

Scenario-based Specification of Security Protocols and Transformation to Security Model Checkers - Koch, Thorsten; Dziwok, Stefan; Holtmann, Jörg; Bodden, Eric (ACM/IEEE 23rd International Conference on Model Driven Engineering Languages and Systems (MODELS ’20))

Model-Driven Information Flow Security Engineering for Cyber-Physical Systems - Gerking, Christopher

Simulationsbasierte Betriebsfestigkeitsanalyse stanzgenieteter Bauteile - Otroshi, Mortaza; Meschut, Gerson; Masendorf, Lukas; Esderts, Alfons

GEMINI-Modellierungssprache für Wertschöpfungssysteme - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

GEMINI-Geschäftsmodellmuster-Kartenset - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodellvalidierung - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)